Proposition of a Model for Selection of the Hybrid Contract Implementation Strategy for a Pilot Project of Regular Road Maintenance in Montenegro - Snežana Rutešić; Jasmina Ćetković; Slobodan Lakić; Angelina Živković; Miloš Knežević (Advances in Civil Engineering)
Performance-based maintenance contracts (PBMCs) are modern contracts that should allow road maintenance entities to contract maintenance activities more successfully and generate money value. In the case of Montenegro, a gradual approach of PBMC introduction is recommended through a hybrid contract for routine road maintenance. Hybrid contract implementation will enable a lower level of client risk in the early stages of PBM contract. Game theory is used for selection of an adequate model for hybrid contract structure in terms of size and nature of the BoQ elements. In addition to the estimated or charged quantities of works from previous contracts, the model also includes parameters that to some extent take into account the experience and expertise of contractors and clients, but also the availability of road data. In order for model to be applied, historical data from traditional road maintenance contracts, which were implemented in the previous period in Montenegro, are used.